2017
DOI: 10.1136/bcr-2016-217337
|View full text |Cite
|
Sign up to set email alerts
|

First reported case of disseminatedNocardia kroppenstedtiisp nov. infection presenting with brain abscess and endocarditis in an immunocompromised patient with mantle cell lymphoma: challenges in diagnosis and treatment

Abstract: A 72-year-old man with a history of blastoid variant stage IV relapsed refractory mantle cell lymphoma presented with new central nervous system (CNS) symptoms. Brain imaging was positive for rim-enhancing lesions along with a mitral valve mass on the echocardiogram. It was a challenge to establish the exact aetiology of these lesions in this patient. He was empirically treated with chemotherapy on the presumption that the brain lesions were secondary to progressive malignancy. However, brain biopsy was negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, numerous case reports and case series have been reported [3-4]. Prevalence of Nocardia in Pakistan is not known and the publications regarding pulmonary nocardiosis in the medical literature are also limited to just case reports, with few case series, which also includes cases of extra-pulmonary nocardiosis [5-6].…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous case reports and case series have been reported [3-4]. Prevalence of Nocardia in Pakistan is not known and the publications regarding pulmonary nocardiosis in the medical literature are also limited to just case reports, with few case series, which also includes cases of extra-pulmonary nocardiosis [5-6].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 demonstrates that 10 (59%) of 17 cases of nocardial brain abscesses showed true restricted diffusion, i.e., hyperintensity on DWI and low signal on ADC maps. 1,6,11,21,27,32,36,39,41,42,46,47,[51][52][53][54] High signal intensity on DWI with low ADC values for cerebral abscesses was first reported by Ebisu et al, 15 with many subsequent studies reporting similar findings. 18,20 In a meta-analysis Xu et al 50 found that DWI had a high sensitivity (0.95) and specificity (0.94) for differentiating brain abscesses from other cystic brain masses, showing it is a reliable method in detecting pyogenic brain abscesses.…”
Section: The Role Of Neuroimaging In Brain Abscessesmentioning
confidence: 96%
“…153 Majeed et al reported a patient with mantle cell lymphoma with disseminated nocardiosis, including brain abscess and endocarditis. 154…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Hence, the use of linezolid has been somewhat limited due to high cost and side effects, but has exceptional activity in vitro and efficacy has been impressive in some clinical series. 131,154,246 Similarly, TMP-SMX can be associated with severe nausea, hyperkalemia, [257][258][259] nephrotoxicity, 259 sudden death (in elderly patients on angiotensin converting enzyme inhibitors or angiotensin receptor blocker), 260 lactic acidosis, 261 and shock (rare allergic reaction), 262 and may not be well tolerated with prolonged use, particularly at high doses.…”
Section: Antimicrobial Susceptibilitymentioning
confidence: 99%